2012
DOI: 10.1016/j.neuroimage.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent attention modulation of human primary visual cortex: A high density ERP study

Abstract: Converging electrophysiological and brain-imaging results show that sensory processing in V1 can be modulated by attention. In this study, we tested the prediction that this early filtering effect depends on the current affective state of the participant. We recorded visual evoked potentials (VEPs) to visual peripheral distractors while participants performed a demanding task at fixation, whose perceptual load was manipulated in a parametric fashion. Crucially, levels of negative affect were either increased o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
89
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(106 citation statements)
references
References 95 publications
13
89
1
Order By: Relevance
“…In line with the brain-imaging evidence and the interpretation put forward by Schmitz and colleagues, in a recent event related brain potential (ERP) study, we showed that affective states reliably influenced the earliest sweep of cortical activation in response to irrelevant neutral peripheral stimuli (Rossi & Pourtois, 2012). This early cortical response was quantified as the amplitude of the C1 (Clark, Fan & Hillyard, 1995;Foxe & Simpson, 2002;Rauss, Schwartz, & Pourtois, 2011), an ERP component classically ascribed to activations in the fundus of the calcarine cortex.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…In line with the brain-imaging evidence and the interpretation put forward by Schmitz and colleagues, in a recent event related brain potential (ERP) study, we showed that affective states reliably influenced the earliest sweep of cortical activation in response to irrelevant neutral peripheral stimuli (Rossi & Pourtois, 2012). This early cortical response was quantified as the amplitude of the C1 (Clark, Fan & Hillyard, 1995;Foxe & Simpson, 2002;Rauss, Schwartz, & Pourtois, 2011), an ERP component classically ascribed to activations in the fundus of the calcarine cortex.…”
Section: Introductionsupporting
confidence: 84%
“…Furthermore, based on our previous ERP findings showing that load-dependent modulatory effects influencing early visual cortex were basically abolished when participants experienced enhanced levels of NA (Rossi & Pourtois, 2012), we also surmised that the transient experience of NA could mimic the effects of perceptual load, namely reduce the precise spatial localization of the peripheral stimuli even under low load.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…We used a validated procedure to induce stress in the lab (Rossi & Pourtois, 2012) and modified the cover story so that it would fit the context of our study.…”
Section: Stress Inductionmentioning
confidence: 99%
“…In line with Rossi and Pourtois (2012), seven visual analogue scales (VAS) were adopted from the Profile Of Mood States (McNair, Lorr, & Dropplemann, 1992) to assess effects of the stress induction on mood. Three scales provided a mean estimate of positive affect (Dutch equivalents of 'energetic', 'satisfied', and 'happy'), another three scales provided a mean estimate of negative affect (Dutch equivalents of 'angry', 'tense', and 'depressed').…”
Section: Stress Inductionmentioning
confidence: 99%